Everything you need to know about Dinosaurs and other Prehistoric creatures - Woodward, John; Hort, John; Prabhakar, Niharika; George, Agey (London : Dorling Kindersley Limited, 2023)
Introduces dinosaurs, including pterosaurs, theropods, and stegosaurs, and explores their anatomy, life cycle, and behavior.
Includes index.
Keywords: Dinosaurs -- Juvenile literature